2023
DOI: 10.1093/schbul/sbac203
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Clozapine and Haloperidol on the 40 Hz Auditory Steady State Response-mediated Phase Resetting in the Prefrontal Cortex of the Female Sprague Dawley Rat

Abstract: Background Neural synchrony at gamma frequency (~40 Hz) is important for information processing and is disrupted in schizophrenia. From a drug development perspective, molecules that can improve local gamma synchrony are promising candidates for therapeutic development. Hypothesis Given their differentiated clinical profile, clozapine, and haloperidol may have distinct effects on local gamma synchrony engendered by 40 Hz clic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 88 publications
1
0
0
Order By: Relevance
“…Lastly, the 40 Hz harmonic took the longest time to emerge, with group-wide synchrony establishing ~ 180 ms from stim onset. This delayed onset of 40 Hz SSHR parallels the slow emergence of the 40 Hz ASSR in humans (Ross et al, 2002), as well as in rodent frontal cortex, as reported recently (Ummear Raza et al, 2023). Thus, it is tempting to speculate that the 40 Hz harmonic may engage the same network or a subset of the network activated by a 40 Hz driving stimulus.…”
Section: Discussionsupporting
confidence: 80%
“…Lastly, the 40 Hz harmonic took the longest time to emerge, with group-wide synchrony establishing ~ 180 ms from stim onset. This delayed onset of 40 Hz SSHR parallels the slow emergence of the 40 Hz ASSR in humans (Ross et al, 2002), as well as in rodent frontal cortex, as reported recently (Ummear Raza et al, 2023). Thus, it is tempting to speculate that the 40 Hz harmonic may engage the same network or a subset of the network activated by a 40 Hz driving stimulus.…”
Section: Discussionsupporting
confidence: 80%